Empowering Vulnerable Adolescents: The Role of Targeted Education and Primary Health Care in Addressing Smoking Risk among Orphaned Adolescents - Marshell Timotius Handoko (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2026)
Background: Indonesia continues to face major challenges in tobacco control, with a high prevalence of smoking, including among adolescents. Orphaned adolescents constitute one of the most vulnerable populations, owing to minimal parental supervision and high exposure to psychosocial stress, both of which increase the risk of smoking behavior. This study aimed to evaluate the effectiveness of an educational intervention on the dangers of smoking for orphaned adolescents at the Maktabul Aitam Orphanage for Orphaned and Underprivileged Children (Panti Asuhan Yatim Piatu & Dhuafa Maktabul Aitam), Ivory Serpong, South Tangerang. Methods: The study employed a quasi-experimental pretest–posttest design involving 23 adolescents who received interactive education. The material covered the dangers of conventional and electronic cigarettes, the effects of passive smoking, and smoking cessation strategies. Data were collected through written pretests and posttests and analyzed descriptively and inferentially using a paired t-test. Results: The results showed that the mean baseline knowledge score was only 43/100, which increased significantly to 95/100 after the intervention (p < 0.001). These findings indicate that contextually tailored education can enhance orphaned adolescents’ understanding of and awareness regarding the dangers of smoking. Conclusion: Life-cycle-based educational programs delivered by family physicians can serve as a key strategy for disease prevention in vulnerable adolescent populations. The integration of such programs into the primary health care system is essential for long-term tobacco control and sustainable health development.